Reversible Posterior Encephalopathy Syndrome and Related Factors: Clinical Cases Study - Talabewui, Abidé; Kombate, Damelan; Seddik-Sifaoui, Lillia; Assogba, Komi; Apetse, Kossivi; Agnon Balogou, Koffi; Cathérine Bachoud Levi, Anne (Journal of Neurological Research And Therapy, 2020)
Background Reversible posterior encephalopathy syndrome (RPE) is a clinical and radiological entity characterized by the acute or subacute fitting of symptoms covering headache, vomiting, visual disturbances, seizures and impairment of consciousness. The pathophysiology of RPE syndrome is poorly described. RPE syndrome is characterized by a reversible cerebral edema of often posterior topography in magnetic resonance imagery (MRI). Cases Presentation We consider RPE syndrome four cases under various conditions that are known as airplane flight, hypertension, non-steroidal anti-inflammatory medication, pregnancy and oldness with several pathologies. The RPE was described with several symptoms like headaches, vomiting, focal motor deficit, paresthesia, seizures, disorders of consciousness and photophobia. The imagery findings were varying from cortical hypersignals in Flair sequences to edema of both cortex and sub cortex. The outcome was good with a complete regression of symptoms and imagery lesions. Conclusion The pathophysiological mechanism of RPE syndrome remains unknown. High blood pressure, renal failure and drugs (anti-depressants, NSAIDs, immunosuppressants) are the most etiological factors. The diagnosis is based on clinical arguments and brain MRI. The main location is posterior. The clinical outcome was good with all the patients in our study, no recurrence was noted.
Keywords: Reversible posterior encephalopathy syndrome; vasogenic brain edema; Hypertension.